Water Quality Index and Health Risks in a Peruvian High Andean River. - Sánchez-Araujo, Víctor (2024)
Water quality in rivers is affected as it passes through urban areas; this situation can be improved with good management of water resources. High Andean rivers require further studies to indicate their quality status. In addition, it is important to estimate the health risks associated with exposure to contaminants in the river water. Therefore, it is proposed to assess the water quality index (WQI) using the National Sanitation Foundation (NSF) model and the health risks in the urban section of the Ichu River in Peru. Six monitoring points were selected in the section of the Ichu River that includes the urbanized part of the city of Huancavelica. The sample was taken during the months of February to April 2021. Critical parameters were analyzed by multivariate statistical analysis as principal components and cluster test. In addition, Pearson’s correlation test was performed, and the water quality status was evaluated using the WQI-NSF model. The Ichu River was of “bad” quality, unfit for human consumption, and confirming the impact of the population on water quality. The WQI-NSF model could be useful for high Andean watercourses suffering from anthropogenic deterioration of quality, with illegal effluent discharges and poor sanitation. There is a high health risk due to fecal coliform contamination from sewage discharges into the river. In addition, the total hazard index indicated that contaminants are causing negative health effects in adult males at a low risk level (risk 2), adult females at a moderate risk level (risk 3), and children at a negligible risk level (risk 1). With the help of this study, an appropriate management plan can be put in place to restore the ecological integrity of the Ichu River